PENGEMBANGAN POTENSI KREATIVITAS SISWA SEKOLAH LUAR BIASA - Zuli Dwi Rahmawati; Bisarul Ihsan (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
Creative potential must be developed in an appropriate way to improve self-quality, self-confidence for students with special needs to eliminate unfavorable assumptions from the surrounding environment which will have an impact on their mental development. The purpose of this community service is to provide experience for them so they can experience firsthand the process of developing creativity activities, know the benefits and get encouragement to be able to hone and develop their potential. Therefore, it is important to carry out creativity development activities to provide skills in the hope of making a positive contribution to their future in society. The creativity potential developed by Bina Harapan SLB students includes batik, cooking and making handicrafts.